THE „LAST MINUTE“ TOURIST ARRANGEMENTS TREND IN SERBIA - Began, Milica P (International Journal of Economic Practice and Policy, 2013)
Tourist agencies in Serbia try to follow trends regardingthe arrangements’ offer. One must admit that the buses owned by the transporters are modern and of a high quality, that there exist good, educated and experienced tourist guides. If one sees the choice of the arrangements, types of the stationary arrangements, accommodation facilities at the destinations and compares them with the same or similar offers that other worldwide tourist agencies have, one will note that the offer in Serbia is not inferior to the offer of the world-known tour-operators such as Dertour. However – many Serbian tourist agencies have the same partners on the destinations (Spain, France, Italy, Greece...) and the same accommmodation facilities (houses and hotels) as the large tour operators. In such a quality offer, in a turbulent market, with the tourists that have limited power of payment, tourist agencies in Serbia are forced to go „below the price“. The term of lowering the prices in tourism is often called „last minute“, and can be present in any form of tourist arrangement. In Serbia it begins to emerge in the last decade, and, after the abolition of visas for traveling abroad, it became omnipresent in tourist offers of Serbian tour operators.